ANALISIS TINGKAT KESEHATAN BANK DENGAN METODE RGEC PADA PT. BANK TABUNGAN NEGARA (PERSERO) TBK - Putri, Putu Ania Cahyani; Suarjaya, A.A. Gede (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
This study aimed to analyze the health of PT. Bank Tabungan Negara (Persero) Tbk period 2013- 2015 RGEC method approach (Risk Profile, Good Corporate Governance, Earnings, Capital). This research is quantitative descriptive method. The variables in this study include Risk Profile using the ratio of Non Performing Loans (NPLs) and loan to Deposite Ratio (LDR), GCG using Composite Rating GCG, Earnings use ratios Return on Assers (ROA) and Net Interest Margin (NIM) and Last Capital uses Adecuacy Capital ratio (CAR). The results showed Bank BTN predicate healthy enough where banks are still quite capable of carrying out risk-based banking management well, so they deserve to be trusted community. However, the calculation of the proportion of non-performing loans NPL ratio is high which causes the value of NPL ratio predicate less healthy so did the LDR is below standard with the predicate less healthy.
Keywords: The Health of Bank, Methods RGEC